Modeling Organizational Mediation A STEM Analysis of Work-Life Balance Determinants - Hendratmoko; Elisabeth Vita Mutiarawati (Global Research on Economy, Business, Communication, and Information, 2025)
This study aims to examine the influence of individual and organizational factors on work-life balance (WLB) as well as the mediating role of organizational factors, and the relationship between individual factors and WLB. This study uses a quantitative method with a total of 165 respondents working in Jakarta during December 2025. Data analysis using PLS-SEM. The results showed that individual factors had a significant effect on WLB (β=0.570) and organizational factors (β=0.650). Organizational factors also had a strong direct effect on WLB (β=0.518). This study also proves that organizational factors function as significant partial mediators with indirect effects = 0.337. This update in the research understands and confirms the mediation mechanism of organizational factors. Implicitly, organizational policies and culture need to be developed to reinforce individual factors towards WLB.